If it's not what You are looking for type in the equation solver your own equation and let us solve it.
X+2/6=X-3
We move all terms to the left:
X+2/6-(X-3)=0
We get rid of parentheses
X-X+3+2/6=0
We multiply all the terms by the denominator
X*6-X*6+2+3*6=0
We add all the numbers together, and all the variables
X*6-X*6+20=0
Wy multiply elements
6X-6X+20=0
We add all the numbers together, and all the variables
20!=0
There is no solution for this equation
| (5x+1)+(4x+17)+90=180 | | 4x-30+3x+10=180 | | (4x-9)+(6x+2)+x=180 | | -5/8(x+3)=10 | | 11x+5=6x+90 | | -4x+6=3x-29 | | 11+18=12x-11x | | 7+d/5=25 | | 6(p+3)=24 | | 10m-2/5=-23 | | -24=4(z+7) | | 0=70-4.9t^2 | | -4×+2y=-16 | | 7x*8x=(5x+3)*(10x-2) | | 5x+3x-60+5x+x=360 | | 3/b+1=5 | | 3x-4x-x=18-6 | | 3(−3x−3)−4x+3=3(−3x−3)−4x+3= 3333 | | 5x+3x+5x+x=300 | | 5(9.7r-4)=16.4 | | 8=1/4(x+16) | | 1/2x-3.2=3/4x/1/5 | | 4(y+3)+y=2 | | x+-9=176 | | 5x-3(2x-1)=1 | | 2x-3(x-3)=1 | | x-6/3=3x+7/4 | | 2k^2-16k=0 | | 5x-2(2x-1)=-2 | | 2(-5-2y)-y=-5 | | (4x+6)-(2x+6)=30 | | 2(3y-1)-y=-2 |